Peran dan Otoritas Dewan Pengawas Syariah dalam Mengawasi Aktivitas Transaksi pada Lembaga Keuangan Syariah di Indonesia - mei santi; Reorycha Risma Putri (LPPM STAI Muhammadiyah Probolinggo, 2025)
The Sharia Supervisory Board (DPS) plays a strategic role in ensuring that the operations of Islamic financial institutions in Indonesia comply with Sharia principles. DPS was established by the Indonesian Ulema Council (MUI) throught the National Sharia Council (DSN) in 1999 to oversee Sharia compliance in the banking and non-bank financial sectors. The primary roles of DPS include providing advice to management, supervising operational activities, end ensuring that the products and services offered comply with DSN fatwas. The legal basis for the existence of DPS is outlined in Law No. 40 of 2007 concerning Limited Liability Companies and Law No. 21 of 2008 concerning Islamic Banking. This study uses a library research method, where library data serve as secondary sources, meaning that the researcher obtains materials from second-hand sources rather than original first-hand data from the field. The study’s findings indicate that DPS plays a strategic role in maintaining the Sharia integrity of Islamic financial instituutions, both through transaction supervision and public education on Islamic finance. DPS also acts as an advisor, helping financial intitutions develop products that meet market needs without violating Sharia principles.